1998
DOI: 10.1103/physrevd.57.4754
|View full text |Cite
|
Sign up to set email alerts
|

Palatini variational principle for an extended Einstein-Hilbert action

Abstract: We consider a Palatini variation on a generalized Einstein-Hilbert action. We find that the Hilbert constraint, that the connection equals the Christoffel symbol, arises only as a special case of this general action, while for particular values of the coefficients of this generalized action, the connection is completely unconstrained. We discuss the relationship between this situation and that usually encountered in the Palatini formulation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…This seems indeed like a precarious balance, so we might be tempted to give up any hope of generalizing the Levi-Civita condition. 3 But motivated by the fact that the relationship between 1 I thank M. S. Narasimhan for pointing out that the higher tensor idea dates back to Riemann. 2 This is an assumption we will make throughout the paper.…”
Section: Ingredientsmentioning
confidence: 98%
“…This seems indeed like a precarious balance, so we might be tempted to give up any hope of generalizing the Levi-Civita condition. 3 But motivated by the fact that the relationship between 1 I thank M. S. Narasimhan for pointing out that the higher tensor idea dates back to Riemann. 2 This is an assumption we will make throughout the paper.…”
Section: Ingredientsmentioning
confidence: 98%
“…Assuming a symmetric metric and a symmetric connection it is straightforward to perform a Palatini variation by varying the connection, compare [4] equation (8) δΓ μν…”
Section: The Jordan Framementioning
confidence: 99%
“…Applying the Palatini variation to the Jordan frame gives a non-metric connection. The only place where Palatini variation of the Jordan frame is looked at is in [4,5] ; however there it is not explicitly stated that the existence of a dilaton forces the geometry of spacetime to be a Weyl geometry, which was suggested on string theory grounds in [23] . There are usually considered to be two types of frame: the Jordan frame and the Einstein frame; perhaps because of the geometry involved it is better to call the Jordan frame with non-metricity the Weyl frame.…”
Section: Introductionmentioning
confidence: 99%
“…A geometrical approach to theories with non-minimal coupling is particularly interesting. According to it, by considering the Palatini variational method a not necessarily Riemannian compatibility condition between the metric tensor and the affine connection-initially taken as independent variables-is obtained [9,10]. Furthermore, it was shown that the geometry that naturally appears when a symmetric affine connection is regarded is the so called integrable Weyl geometry, where the scalar field takes part together with the metric tensor in the description of the gravitational field.…”
Section: Introductionmentioning
confidence: 99%